Relevansi Hukum Kodrat Stoa terhadap Disrupsi Kecerdasan Buatan - Theo, Yohanes (Media: Jurnal Filsafat dan Teologi, 2024)
Artificial intelligence begins to be treated as a conscious entity;  it can feel guilty, and provide improvements for more perfect results in the future. I raises the important question: is human life still secure? This article discusses the relevance of Stoic natural law in regard with the disruption of artificial intelligence. This research was designed as a literature review. In the midst of the progress of artificial intelligence, this article aims to discuss human nature from the perspective of Stoicism's human philosophical thought, especially one of nature. The Stoics were one of the academic   schools in the Hellenistic era that specifically paid attention to the concept of nature. The core of their moral teachings is found in the imperative "live according to nature". Stoic teachings about nature can be achieved by being a true human being, and choosing the right things in certain situations. By understanding the human nature, the disruption of the era of artificial intelligence does not need to be feared excessively. Human being is based on their conscience, an internal force that will direct them to choose what is morally good and not vice versa. An inner voice will never be possessed by artificial intelligence.